2013
DOI: 10.1007/s11356-013-1690-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary antioxidants (selenium and N-acetylcysteine) modulate paraoxonase 1 (PON1) in PCB 126-exposed rats

Abstract: The environmental pollutants polychlorinated biphenyls (PCBs), especially dioxin-like PCBs, cause oxidative stress and associated toxic effects, including cancer and possibly atherosclerosis. We previously reported that PCB 126, the most potent dioxin-like PCB congener, decreases antioxidants such as hepatic selenium (Se), selenium-dependent glutathione peroxidase and glutathione (GSH), but also increases levels of the anti-atherosclerosis enzyme paraoxonase 1 (PON1) in liver and serum. To probe the interconne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 78 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Paraoxon and phenylacetate were used as two individual substrates in PON1 activity measurements as described [27] . Briefly, the enzyme activities were determined spectrophotometrically following the initial rate of substrate hydrolysis to p-nitrophenol (412 nm) or phenol (270 nm), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Paraoxon and phenylacetate were used as two individual substrates in PON1 activity measurements as described [27] . Briefly, the enzyme activities were determined spectrophotometrically following the initial rate of substrate hydrolysis to p-nitrophenol (412 nm) or phenol (270 nm), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Several in-vivo studies have shown an increase in PON1 activity/expression following vitamin C consumption [11], vitamin E consumption [12], carotenoids [13], mono-and polyunsaturated fatty acids [14], selenium consumption [15], and polyphenol supplementation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Paraoxonases are important antioxidant enzymes in tissues and blood and our previous studies indicated that at least one PCB congener, PCB126, the most potent AhR agonist among all PCBs, can influence the PON1 gene expression and enzyme activity levels in rats (Shen et al 2014, Shen et al 2012). This raised two questions: 1.…”
Section: Discussionmentioning
confidence: 99%
“…However this potential chemoprotection option needs to be carefully approached as our results with N-acetyl cysteine and selenium in PCB126 exposed rats have shown (Shen et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation